Validación del Cuestionario de Creencias Irracionales (TCI) en población colombiana (2010)
ABSTRACT: The purpose of the research presented in this paper was the validation of the Irrational Beliefs Questionnaire (IBQ) in the colombian population. The IBQ evaluates the following irrational beliefs: need for approval by others, high self-expectations, guiltiness, control of emotions, avoidance of problems, psychological dependence, helplessnes when facing change, and perfectionism. For this research 368 people of both genders and chosen from diverse socioeconomic stratas were tested, 136 males (37 %) and 232 women (63 %). The ages ranged between 18 and 70 years old, with a median of 32 yrs, and a standard deviation of 10.5 yrs.